‘Navelina’ oranges submitted to pre-harvest resistance inducers - Kirinus, Marines Batalha Moreno; Barreto, Caroline Farias; Silva, Pricila Santos da; Oliveira, Roberto Pedroso de; Malgarim, Marcelo Barbosa; Fachinello, José Carlos (Acta Scientiarum. Agronomy, 2018)
The objective of this study was to evaluate the physical-chemical characteristics, rot index and bioactive compounds of ‘Navelina’ oranges under postharvest refrigerated storage conditions after pre-harvest resistance induction in crops from 2015 and 2016. The field experimental design was completely randomized blocks. The treatment factors were composed of the following resistance inducers: noresistance inducer (control), selenium (Se), silicon (Si), acibenzolar-s-methyl (ASM), methyl jasmonate (MeJa), thiamethoxam (TMT) and imidacloprid (IMI). In the laboratory, the experimental design was the same as that in the field, but it used a two-factor scheme instead of a unifactorial scheme. In the two-factor scheme, factor A was composed of the abovementioned resistance inducers, and factor B was composed of the refrigerated storage periods (zero and 30 days). The analyses investigated the coloration, fresh mass loss, rot index, soluble solids, pH, titratable acidity, SS/TA ratio, ascorbic acid, total phenolic compounds and antioxidant capacity of the oranges. The application of pre-harvest resistance inducers was efficient in maintaining the physical-chemical characteristics of the ‘Navelina’ oranges in postharvest, increasing their bioactive compounds in comparison to the control. The resistance inducers Se, Si, MeJa, and IMI reduced rot rates, while ASM and MeJa prevented fresh fruit mass loss.